Development of Learning Model of Project-Based Learning Integrated with Entrepreneurship in The Productive Learning of Motorcycle Tune-Up Competence - Ariwibowo, Bayu; Slamet, Achmad; Syamwil, Rodia (Universitas Negeri Semarang, 2018)
Unemployment of graduates of Automotive Engineering expertise program of Vocational High School (SMK) can be overcome with entrepreneurship. The obstacle is that students are not ready to become entrepreneurs. Learning process at school needs to be analyzed to find new learning models that enhance students' entrepreneurship skills which is in accordance with the expertise program. This study aims to analyze the factual conditions of productive learning of motorcycle tune-up competence and entrepreneurial learning in SMK, to analyze conceptual models developed, to determine hypothetical models, to analyze student learning outcomes using hypothetical models, and to determine the final model of learning. The method used in this research is research and development, carried out by conducting preliminary studies, model development, product testing, and final model determination. The result shows that factually productive learning of motorcycle tune-up competence with entrepreneurship lesson are separated. The conceptual model designed using the syntax of project-based learning model has entrepreneurship approach in productive learning, but still requires improvement. After the improvement, there comes a hypothetical model with the principle of integrating productive learning with entrepreneurial activity, and the learning is oriented towards a modified project-based learning model. The model is well implemented because the experimental class’ learning result is better than the control class’ learnng result. The value of technical skill and entrepreneur skills of experimental class students increased significantly, thus the final model of learning used hypothetical model with the learning model name is PjBL In Entre (Project-Based Learning Integrated with Entrepreneurship).